Determinação da concentração de tensões em furos circulares de placas planas cisalhadas - Silva, Rouverson Pereira da (1995)
This work presents the study of the stress concentration around circular holes on shear flat plates, with the photoelasticity techuique and the numerical analysis of finite elements. The parame.er investigated was . , ripfined bv ratio of hole diameter to plate the circular hole locations, delineo oy h Qn+riritv of the hole with respect to the centre of the width, d/a, and by eccentricity , .. Q tu;c nuroouse a test assembly was idealized with plate, L/a. To achieve this purpuua four articculated Steel members, ,o apply the shear loading on the plates. The experimental results obtained for this loading were monitora,ed with • 1 onalvsis of finite elements. In addition, similar the results of the numerical analysis o , , „7í>re loaded to shear in combination with biaxial plates with circular holes, w . ctrPSS concentration were obtained by three- compression, where the • ■* nr çtress freezing technique. The results were dimensiona! photoelastrc.ty or stress lonlpnt<; in the same loading conditions. In this also monitorated by fimte elements, „„ presented and discussed, and compared w.th studies, important results c , . Works concerning the buckl.ng of plates w.th results published by other circular holes.